EXPOSURE OF THE STUDENTS OF THE SECONDARY SCHOOL OF ELECTRICAL ENGINEERING ”NIKOLA TESLA” TO WIRELESS ELECTROMAGNETIC RADIATION - Jevtic, Radoje; Jankovic, Ivana (HEALTH CARE, 2022)
Introduction/Aim: Wireless electromagnetic radiation from routers is an everyday occurrence in the life and work of modern man. They are widely used in many professional, public and domestic facilities, which means that people of all ages can be constantly exposed to electromagnetic radiation from these devices. The aim of this study was to determine the electric field strength, the magnetic field strength, and the electromagnetic exposure of students in different laboratories of the Secondary School “Nikola Tesla”, depending on the type of routers installed in them, as well as to check some of the obtained results with the help of the appropriate software program of high-frequency (High-Frequency Simulation Software – HFFSS) for the simulation of electromagnetic radiation through different environments. Method: Measurements of electric and magnetic field strength, as well as electromagnetic exposure, were carried out using the measuring instrument Spectran HF 60105, on four different types of routers installed in four laboratories of the Secondary School of Electrical Engineering “Nikola Tesla” in Niš. Measurements were realized on each router, through five horizontal and five vertical positions, with a distance of 45o in relation to the horizontal and normal axis of the router, and with spaces of 1 cm, which gives a total number of one thousand measurements. Results: The measured results obtained on four different routers that operated at a frequency of 2.4 GHz for the electric field strength (measured in millivolts per meter), magnetic field strength (measured in microampere per meter) and electromagnetic exposure (in microWatts per square centimeter) were below the limit values defined by standards. The achieved results were verified only for the router TL-WR841HP with the help of HFSS for the simulation of electromagnetic radiation through different environments. The result of the simulation check practically confirms the reliability of the measured results for TL-WR841HP router. Conclusion: Measuring and monitoring electromagnetic radiation is a very important task aimed at preserving and improving the quality of the working and living environment, as well as the quality of life and health of people and children. Software programs for the simulation of electromagnetic radiation can be used when it is not possible to carry out experimental measurements due to technical problems, hindered access to the device, danger of excessive radiation or some other reasons.